The Effects of Vertical and Horizontal Power on Individual Motivation and Satisfaction1 - Drake, Bruce H.; Mitchell, Terence R. (Academy of Management Journal, 1977)
This research examined the effects of both vertical and horizontal power on participants in an experimental decision task. Both power variables had substantial positive impacts on individual motivation and satisfaction. These results strongly suggest that both power dimensions are important for understanding people's reactions to participation in the decision process.